2018
DOI: 10.1155/2018/5472018
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review: The Trajectory of Recovery of Participation Outcomes following Stroke

Abstract: Participation is a central concept in health and well-being and healthcare, yet operationalizing this concept has been difficult. Its definition, uses in healthcare, and impacts on recovery require ongoing research. Our review question goes like this: from the longitudinal evidence investigating participation among stroke survivors, what are the patterns of participation recovery in stroke survivors over time, and what interventions are used to improve participation? To fully understand these questions, we als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 101 publications
0
47
0
Order By: Relevance
“…15,51,52 Participation Patients and their parents in this study reported participation restrictions in all domains of participation (median total score 82.5 (IQR 68.8, 92.3), 91.1 (80.0, 96.9), respectively), supporting earlier studies in this patient population (pediatric ABI 27,53 ; adult mTBI 54 ; stroke. 55 ) In the current study, AYAs reported significantly more participation restrictions than their parents, in home, community and school activities. Previous research on patientand parent-reported participation with the CASP has found patients reporting less participation restrictions than their parents.…”
Section: Fatiguementioning
confidence: 47%
“…15,51,52 Participation Patients and their parents in this study reported participation restrictions in all domains of participation (median total score 82.5 (IQR 68.8, 92.3), 91.1 (80.0, 96.9), respectively), supporting earlier studies in this patient population (pediatric ABI 27,53 ; adult mTBI 54 ; stroke. 55 ) In the current study, AYAs reported significantly more participation restrictions than their parents, in home, community and school activities. Previous research on patientand parent-reported participation with the CASP has found patients reporting less participation restrictions than their parents.…”
Section: Fatiguementioning
confidence: 47%
“…The SIS-P is the most frequently used scale to measure participation following stroke (15). The SIS-P is a self-report questionnaire containing 8 questions that ask the participant to rate how much of the time he or she has been limited in the past 4 weeks in work, social, productive activities and control over one's life (16).…”
Section: Methodsmentioning
confidence: 99%
“…However, most studies currently continue to emphasize measurement and intervention in terms of motor function and mobility. Therefore, further research focusing on achieving meaningful participation and improving QoL, extending beyond impairment remediation approaches, is still needed (10, 17).…”
Section: Introductionmentioning
confidence: 99%